Penerapan Hukum Serta Penanggulangan Tindak Pidana Penyalahgunaan Narkotika Terhadap Anak Dibawah Umur - Aduba Mauzihan Amrich (Pusat Riset dan Inovasi Nasional, 2024)
The abuse of narcotics is currently very concerning, as it is not only among adults but also occurs among minors. Drug abuse is a crime that can endanger a child's growth and future. The act of drug abuse committed by minors is an illegal act. The purpose of this research is to understand how Law Number 35 of 2009 on Narcotics Jo Law Number 35 of 2014 on Child Protection. The method used in this research is normative legal research, which is research that produces data and views that develop in legal science and law related to the title raised by the author.